STRUKTURALISME DINAMIK DALAM NOVEL A STUDY IN SCARLET KARYA SIR ARTHUR CONAN DOYLE (SUATU KAJIAN KRITIK SASTRA) - Yolanda Naomi Pardede; Syahrul Ramadhan (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Literary works are all types of compositions created based on human imagination or imagination and using language as the medium. A good literary work is a literary work that can present a social reality based on heuristic experience and can inspire its audience. A novel is a form of work that contains characters, a series of structured events and can be used as a life experience and provide education to its readers. There are many ways to analyze or study a novel, one of which is dynamic structuralism. This research examines the novel A Study in Scarlet by Sir Arthur Conan Doyle using a dynamic structuralism approach and descriptive qualitative research methods. The data collection techniques used by researchers are observation, reading and note-taking techniques. The data analysis techniques carried out by researchers include data reduction, data presentation, and drawing conclusions. Keywords: dynamic structuralism